The effects of financial literacy, self-efficacy and self-coping on financial behavior of emerging adults - Chong, Kok Fei; Sabri, Mohamad Fazli; Magli, Amirah Shazana; Abd. Rahim, Husniyah; Mokhtar, Nuradibah; Othman, Mohd Amim (Korea Distribution Science Association, 2021)
This study examines the relationship between financial behavior, financial literacy, self-efficacy, and self-coping among emerging adults. The study population is 790 respondents from 11 Credit Counselling and Debt Management (CCDM). Statistical Package for Social Science (SPSS) was used to analyze Pearson Correlation and Multiple regression. It was used to determine the relationships and recognize determinants of emerging adults' financial behavior respectively. In this study, financial literacy, self-efficacy, self-coping, and financial behavior variables were entered into the regression. A total of 790 respondents aged 40 and below were selected. An independent sample t-test was administered to compare the financial behavior scores for females and males. The results reveal that there was significant difference in the mean of financial behavior scores for females (M = 87.20, SD = 18.00) and males (M = 89.70, SD = 16.80; t (765) = 2.010, p = 0.045, two-tailed). The multiple regression results indicate that the model explained 13.4% of the variance in financial behavior, which is predicted significantly by the model (F = 38.361, p = 0.000). This study will be beneficial to policymakers to improve living conditions and to promote good financial behavior, financial literacy, self-efficacy as well as self-coping especially for emerging adults in Malaysia.